Miejsce niewolników w rodzinie chrześcijańskiej według Jana Chryzostoma - Duda, Jerzy (Vox Patrum, 2009)
The early Christian Church did not take up any revolutionary action aiming at reforming or abolishing the so much bound with the Roman society structure slavery. Instead, it worked out a new ‘theoretical’ and characterized by humanism attitude, which is reflected and strengthened by John Chrysostom. The ‘golden mouthed’ admits that slavery is a binding and allowed by God’s Providence state, and he accepts the power of a master over a belonging to the Christian family slave. A slave should not rebel against his unjust situation but try to serve his master and family as if he actually saved his Saviour Redeemer. And that is because slaves are in nature free people and as any other people are the children of the same God. That is why he demands treating a slave as a human being and respecting his dignity. Also, he suggests a new notion of a slave being a good and obedient to his master person since, as he believes, a change in the present negative stereotype will contribute to some improvement in the existential situation, or in some time may lead to the reform of the social-economic state system.